Non-communicating multiseptate gall bladder and choledochal cyst: a case report and review of publications. Issue 6 (June 1993) - Tan, C E; Howard, E R; Driver, M; Murray-Lyon, I M
Abstract : A 14 year old girl with multiseptate gall bladder and cystic dilatation of the biliary tree is presented. This is the 20th published case report of patients with multiseptate gall bladder and only the second to be associated with a choledochal cyst. The cystic spaces of the gall bladder did not communicate with the neck of the gall bladder or the rest of the biliary tree, and this unusual feature has not been previously described. A multiseptate gall bladder with a normal biliary tree commonly causes symptoms suggestive of cholecystitis, although gall stones are seldom present. Diagnosis is confirmed by an oral cholecystogram or ultrasound scan that may show the fine intraluminal septae, and these features should be looked for in patients with biliary symptoms without biliary calculi. Cholecystectomy is curative for the isolated gall bladder anomaly but hepaticojejunostomy may be necessary for an associated choledochal cyst.